Reproductive biology of the two deep-sea chimaerids, longnose spookfish (Harriotta raleighana) and Pacific spookfish (Rhinochimaera pacifica). (February 2017) - Finucci, B.; Dunn, M.R.; Jones, E.G.; Anderson, J.
Abstract: The family Rhinochimaeridae, the long-nose chimaerids, consists of eight species across three genera, two of which occur in New Zealand waters. Very little is known about the biology of the rhinochimaerids. Longnose spookfish, ( Harriotta raleighana, Goode and Bean, 1895 ), and Pacific spookfish, ( Rhinochimaera pacifica, Mitsukuri, 1895 ), were collected from research trawl surveys and by commercial fishing vessels around New Zealand at depths between 400 and 1300 m. A total of 300 H. raleighana were caught which varied in length from 18.7 to 90.4 cm chimaera length (CL), and 168 R. pacifica at lengths of 20.9–139.9 cm CL. External assessment of male claspers and female gonad mass and oviducal gland width were the best indicators for maturity. Both species matured at a large proportion of their maximum length. Length at maturity was estimated at 62.8 cm CL and 75.8 cm CL for male and female H. raleighana respectively, and 105.3 cm CL and 125.0 cm CL for male and female R. pacifica . Fecundity was low and measured up to 27 eggs for H. raleighana, and 31 eggs for R. pacifica . Sperm storage was confirmed in females of both species. Sexual dimorphism in snout length was found in H. raleighana, where male relative snout size increased at sexual maturity, suggesting the snout is a secondary sexual characteristic. This study contributes to a better understanding of the life histories of H. raleighana and R. pacifica and their vulnerability to exploitation as fisheries bycatch. Highlights: Reproductive biology of two poorly known deep-sea chimaeras H. raleighana and R. pacifica is described. Both species matured at a large proportion of their maximum length, suggesting late maturation. Sperm storage tubules (SSTs) and sperm bundles were identified in the terminal zone of the oviducal gland. Sexual dimorphism in snout length was found in H. raleighana, suggesting the snout is a male secondary sexual characteristic. All known publications on holocephalan reproduction are reviewed.